Perancangan Sistem Proteksi Baterai Berbasis Load Shedding Pada Sistem Hybrid (PLTS-PLTB) Rumah Apung - Rizkyanto Malah; Zefanya Aring; Randy Pramudya Anung; Leony Ariesta Wenno; Fanny Jouke Doringin (CYCLOTRON, 2026)
Abstract— In recent years, the use of renewable energy has increased significantly to reduce dependence on fossil fuels and cut carbon emissions. One emerging solution is a hybrid power generation system that combines solar power plants (SPP) and wind power plants (WPP), particularly in coastal areas such as the floating houses on Malalayang Beach. However, the battery-based energy storage system in this setup lacks adequate protection mechanisms, making it susceptible to overcharging and over-discharging conditions that can degrade battery performance and shorten its lifespan. This study aims to design an IoT-based battery protection system for the SPP-WPP hybrid system. The method used is Research and Development (R&D) through the stages of system design, fabrication, and testing. The system is designed using a PZEM-017 sensor for measuring electrical parameters, an ESP32 as the main controller, and a relay as the actuator for a multi-level load shedding mechanism. System monitoring is performed in real-time via the Blynk platform. Test results show good voltage measurement accuracy, with error values ranging from 0.55% to 0.82% and an average of 0.686% when compared to a multimeter. The protection system also functions as designed, where load disconnection occurs gradually based on battery voltage: 24 V (all loads active), 23 V (load 1 off), 22 V (loads 1 and 2 off), 21 V (loads 1, 2, and 3 off), and 20 V (all loads off). This system is capable of consistently responding to voltage changes without false triggers. It enhances safety, reliability, and battery lifespan, and supports Sustainable Development Goals (SDGs) 7 and 13.